2022
DOI: 10.21203/rs.3.rs-1199477/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Level of Maternal Health Literacy (MHL) and Associated Factors among Pregnant Women Attending Antenatal Care Clinics of Public Health Facilities in Southern Ethiopia, 2021: A Facility Based Crossectional Study with Linear Models

Abstract: Background: Maternal Health Literacy (MHL) is defined as a woman's cognitive and social abilities and motivation to access, assess, understand and use basic health information and services to make informed decisions that protect and promote their own and their children's health. Pregnant women's HL will enhance the effectiveness and long-term viability of those services by allowing them to get health-related knowledge and behaviours during this critical period. As a result, this study aimed at assessing the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(38 reference statements)
0
3
0
2
Order By: Relevance
“…Various studies have been conducted in different contexts to investigate the level of HL and NL. The HL and NL level in some of these studies has been reported as adequate and sufficient ( Fallah Morteza-Nejad et al, 2019 , Habte et al, 2022 , Moradzadeh et al, 2022 ). Various factors affect the HL and NL level.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Various studies have been conducted in different contexts to investigate the level of HL and NL. The HL and NL level in some of these studies has been reported as adequate and sufficient ( Fallah Morteza-Nejad et al, 2019 , Habte et al, 2022 , Moradzadeh et al, 2022 ). Various factors affect the HL and NL level.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that there is a relationship between parents' NL and children's food quality, income, parents' age, parents' education level. It has been seen that there is a relationship between education level and obesity in high-income countries such as the United States ( Gibbs et al, 2016 , Habte et al, 2022 ). It has also been observed that there is a positive relationship between the level of HL and the level of education ( Habte et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daugelis tyrėjų pastebi teigiamą aukšto sveikatos raštingumo įtaką dabartinei ir būsimai asmens sveikatai [4]. Žemesnis sveikatos raštingumas siejamas su prastesniu rūpinimusi savo sveikata, su sveikatai nepalankia elgsena (pvz., sveikatai žalingų medžiagų vartojimu [5]), su, prastesne subjektyviai vertinama fizine ir psichine sveikata [6,7)], dažnesne hospitalizacija [6] Tėvų sveikatos raštingumas yra labai svarbus veiksnys, lemiantis vaikų sveikatos būklės skirtumus [8]. Žemesnio sveikatos raštingumo tėvų grupėje dažniau pastebimi kūdikių ir vaikų elgesio sunkumai (pvz., prastas miegas [9]), šie tėvai taip pat dažniau susiduria su netikėtais ir nenumatytais vaikų sveikatos sutrikimais (infekcinėmis ligomis, susižalojimais, apsinuodijimu medikamentais), dėl jų dažniau lankosi skubios pagalbos skyriuose [10].…”
Section: įVadasunclassified
“…Žemesnio sveikatos raštingumo tėvų grupėje dažniau pastebimi kūdikių ir vaikų elgesio sunkumai (pvz., prastas miegas [9]), šie tėvai taip pat dažniau susiduria su netikėtais ir nenumatytais vaikų sveikatos sutrikimais (infekcinėmis ligomis, susižalojimais, apsinuodijimu medikamentais), dėl jų dažniau lankosi skubios pagalbos skyriuose [10]. Moterys, kurių sveikatos raštingumas žemas, rečiau lankosi pas nėštumo priežiūros specialistus, jos gali būti prasčiau pasiruošusios gimdymui [5].…”
Section: įVadasunclassified